Chapter Creatività e nuova cultura organizzativa - Rossi, Bruno (Studies on Adult Learning and Education, 2022)
The essay discusses creativity as a guiding idea to be entrusted with the task of building a new organizational culture, through which the person can witness at once the recognition and appreciation of his or her powers and the renewal of the context whose development and success are increasingly inseparable from the practice of divergent intelligence of individuals and groups. Above all, the creative person is able to give quality to work and working life, survival and competitive strength, particularly, by virtue of his or her ability to respond with an attitude of confrontation towards complexity, approach problems originally, appropriately and realistically, strive not only to solve them but also to find new ones, to cultivate initiative and autonomy, to strive to go beyond the current, the "not-yet-being," the already given, the already accomplished, the already acquired, to be willing to tread unfamiliar and tested, even unknown routes and thus produce new and useful (creative, precisely) professional knowledge that is increasingly indispensable today to make the organization more competitive.